2013
DOI: 10.1128/ec.00159-13
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Molecular Basis of Temperature-Dependent Genetic Regulation in Penicillium marneffei

Abstract: c Penicillium marneffei is an opportunistic fungal pathogen endemic in Southeast Asia, causing lethal systemic infections in immunocompromised patients. P. marneffei grows in a mycelial form at the ambient temperature of 25°C and transitions to a yeast form at 37°C. The ability to alternate between the mycelial and yeast forms at different temperatures, namely, thermal dimorphism, has long been considered critical for the pathogenicity of P. marneffei, yet the underlying genetic mechanisms remain elusive. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 98 publications
1
21
0
Order By: Relevance
“…24 Our previous comparative transcriptomic analysis (unpublished data) has indicated that the TmPlb1 gene is overexpressed in the yeast phase (1.60-fold). In this study, sensitive qRT-PCR was used to analyze the differential expression of TmPlb1 between the mycelial phase and yeast phase, and the results confirmed that the mRNA level of TmPlb1 increased in the pathogenic yeast phase (1.85-fold).…”
Section: Discussionmentioning
confidence: 97%
“…24 Our previous comparative transcriptomic analysis (unpublished data) has indicated that the TmPlb1 gene is overexpressed in the yeast phase (1.60-fold). In this study, sensitive qRT-PCR was used to analyze the differential expression of TmPlb1 between the mycelial phase and yeast phase, and the results confirmed that the mRNA level of TmPlb1 increased in the pathogenic yeast phase (1.85-fold).…”
Section: Discussionmentioning
confidence: 97%
“…6). In all cases where RNAseq data was available [3, 4, 4547] (S6 Data), the distribution of yeast/hyphal expression for the orthologs of the filament-associated genes was biased towards showing hyphal expression rather than mimicking the distribution of the global transcriptome (p < .05, Wilcoxon test; S7 Data). In contrast, in Ophiostoma novo-ulmi (the causative agent of Dutch elm disease and the only other dimorphic ascomycete for which we were able to obtain RNAseq data [48]), the distribution of yeast/hyphal expression for the filament-associated regulon was indistinguishable from the rest of the transcriptome.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study of the genome structure of T . marneffei identified an increase in number of genes with TRSs compared to three other pathogenic and non-pathogenic filamentous fungi (Yang et al 2013).…”
Section: Resultsmentioning
confidence: 99%